Adaptable graphitic C6N6-based copper single-atom catalyst for intelligent biosensing - Hong, Qing; Yang, Hong; Fang, Yanfeng; Li, Wang; Zhu, Caixia; Wang, Zhuang; Liang, Sicheng; Cao, Xuwen; Zhou, Zhixin; Shen, Yanfei; Liu, Songqin; Zhang, Yuanjian (Nature communications, 2023)
Self-adaptability is highly envisioned for artificial devices such as robots with chemical noses. For this goal, seeking catalysts with multiple and modulable reaction pathways is promising but generally hampered by inconsistent reaction conditions and negative internal interferences. Herein, we report an adaptable graphitic C 6 N 6 -based copper single-atom catalyst. It drives the basic oxidation of peroxidase substrates by a bound copper-oxo pathway, and undertakes a second gain reaction triggered by light via a free hydroxyl radical pathway. Such multiformity of reactive oxygen-related intermediates for the same oxidation reaction makes the reaction conditions capable to be the same. Moreover, the unique topological structure of Cu SA C 6 N 6 along with the specialized donor-π-acceptor linker promotes intramolecular charge separation and migration, thus inhibiting negative interferences of the above two reaction pathways. As a result, a sound basic activity and a superb gain of up to 3.6 times under household lights are observed, superior to that of the controls, including peroxidase-like catalysts, photocatalysts, or their mixtures. Cu SA C 6 N 6 is further applied to a glucose biosensor, which can intelligently switch sensitivity and linear detection range in vitro. Catalysts with multiple and modulable reaction pathways are promising but generally hampered by inconsistent reaction conditions and negative internal interferences. Herein, the authors report an adaptable graphitic C6N6-based copper singleatom catalyst